GARCH (1,1) models and analysis of stock market turmoil during COVID-19 outbreak in an emerging and developed economy - Budi Setiawan; Marwa Ben Abdallah; Maria Fekete-Farkas; Robert Jeyakumar Nathan; Zoltan Zeman (Journal of Risk and Financial Management, 2021)
COVID-19 pandemic has led to uncertainties in the financial markets around the globe. The pandemic has caused volatilities in the financial market at varying magnitudes, in the emerging versus developed economy. To examine this phenomenon, this study investigates the impact of COVID-19 pandemic on stock market returns and volatility in an emerging economy, i.e., Indonesia, versus developed country, i.e., Hungary, using an event-study approach methodology utilizing GARCH (1,1) model. In this study, the Jakarta Composite Index (JCI) and the b (BUX) data were obtained from Investing and Bloomberg, covering two global events observed within the selected period from 27 September 2006 to 31 August 2021. The data is compared with the stock market volatility data from the global financial crisis in 2007/08. Findings reveal that the recent COVID-19 pandemic had negative stock market returns at a greater magnitude compared to the global financial crisis, in both the emerging and developed economy's equity market. Stock markets in Indonesia and Hungary have experienced volatility during the crisis. While comparing the result between COVID-19 and the global financial crisis, we found that the volatility on the stock markets is higher in the COVID-19 pandemic than during the global financial crisis. The higher stock market negative returns and volatility during the COVID-19 pandemic triggered the lockdown and limited economic activities, which impacted supply and demand shock. The virus's propagation and mutation are continually evolving, reminding us that the pandemic is far from over. Developed countries with larger fiscal space seem to find it easier to make responsive policies than countries with a tighter financial budget. Fiscal and monetary policies seem to be a quick solution to stabilize the economy and maintain investor confidence in the Indonesian and Hungarian capital markets. Furthermore, the extension of stock market volatility understanding ensures relevant information for investors, which benefits to mitigate the risk and build sustainable investments of the unprecedented events and enables the promotion of Sustainable Development Goal number 8 (SDG8) to communities, with access to financial products including the stock market, especially during economic and financial uncertainties.
Keywords: 330; Budapest Stock Exchange; Jakarta Composite Index; stock market reaction; unprecedented events; financial sustainability; SDG8